A note on some distance-based topological indices of circulant network Cn(1, a). (2nd January 2022) - Antalan, John Rafael M.; Campeña, Francis Joseph H.; Ibañez, Edwin D.
Abstract: Let Г be a simple connected graph/network with vertex set V (Г) and edge set E (Г). A topological index is a real number associated to Г that characterizes its topology and is invariant under graph automorphism. If υi and υj are vertices in V (Г), the distance between them denoted by d Г ( υi, υj ) refers to the length of the shortest path that connects υi, and υj . A topological index is said to be distance-based if its computation involves distance between vertices. Recently, the exact value of some distance-based topological indices namely Wiener, hyper-Wiener, and Schultz molecular topological index of the circulant network Cn (1, a ) for a = 2, 3, 4, and 5 were computed. In this paper, we use the breadth-first search method to compute for some distance-based topological indices of the circulant network Cn (1, a ) where a = 6 and . We also provide a general formula for the computation of the Wiener, Schultz, and Gutman index of the circulant network Cn (1, a ) where .